Pelatihan Pembuatan Telur Asin Kepada Pinsar Petelur Nasional Wilayah Lampung - safitri, yuni; Tamrin, Tamrin; Warji, Warji; Hidayat, Kuswanta Futas; Hasani, Qadar (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2025)
A salted egg maker has been developed by the Agricultural Engineering Department. The tool is the third generation, with a glass container for the salt solution. This ensures the container is leak-proof and corrosion-resistant, as previous salted egg makers were made of metal. This training aims to teach the public how to use the tool. The tool is made of glass, making it susceptible to breakage or cracking. This community service program involves lectures and demonstrations. The activity was conducted in the Integrated Field Laboratory of the Faculty of Agriculture. Participants were invited to the Integrated Field Laboratory. The materials provided included: 1. Introducing the modified tool to the participants, 2. Teaching participants how to use the modified tool, and 3. Teaching them how to store it properly. It is hoped that those who participate in this training will be able to apply and disseminate the knowledge gained after the training.